Correlations among peripheral blood markers, white matter hyperintensity, and cognitive function in patients with non-disabling ischemic cerebrovascular events - Li, Binghan; Du, Bingying; Gu, Zhengsheng; Wu, Chenghao; Tan, Yuhao; Song, Chenrui; Xu, Yawen; Yin, Ge; Gao, Xin; Wang, Weisen; Sun, Xu; Bi, Xiaoying (Frontiers in Aging Neuroscience, 2022)
BACKGROUND: Both inflammation and cerebral white matter injury are closely associated with Vascular Cognitive Impairment (VCI). The aim of this study was to analyze the correlation between peripheral serological markers, white matter injury and cognitive function in patients with Non-Disabling Ischemic Cerebrovascular Events (NICE), to identify potential biological markers that are valuable in the diagnosis and prediction of VCI, and to provide a basis for early diagnosis and intervention of VCI. The study was conducted to identify potential biological markers that are valuable in the diagnosis and prediction of VCI, and to provide a basis for early diagnosis and intervention of VCI. Results: Among 151 patients with NICE, 95 were male and 56 were female, and lymphocyte count (OR=0.405, P=0.010), red blood cell count (OR=0.433, P=0.010), and hemoglobin (OR=0.979, P=0.046) were protective factors for cognitive function in patients with NICE. sWMH patients had a higher age, higher granulocyte lymphoid ratio (NLR) and neutrophil percentage, while MOCA score, hemoglobin and lymphocyte percentage were lower than in the mWMH group. In mWMH patients, lymphocyte count (AUC=0.713, P=0.003), white blood cell count (AUC=0.672, P=0.011), red blood cell count (AUC=0.665, P=0.014) and hemoglobin (AUC=0.634, P=0.047) had good predictive value for the diagnosis of VCI, with lymphocyte count had the highest value. In patients with sWMH, no statistically significant differences were found between VCI and patients with normal cognitive function. CONCLUSION: Lymphocyte count, red blood cell count, and hemoglobin are independent protective factors for cognitive function in NICE patients and can be used as potential biomarkers to distinguish VCI in NICE patients and are applicable in subgroups of patients with mWMH.